CD26 Expression on T Helper Populations and sCD26 Serum Levels in Patients with Rheumatoid Arthritis. - Oscar J Cordero; Rubén Varela-Calviño; Tania López-González; Cristina Calviño-Sampedro; Juan E Viñuela; Coral Mouriño; Íñigo Hernández-Rodríguez; Marina Rodríguez-López; Bruno Aspe de la Iglesia; José María Pego-Reigosa (PLoS ONE, 2015)
We studied dipeptidyl peptidase IV (DPP-IV, CD26) expression in different T helper cells and serum soluble DPP-IV/sCD26 levels in rheumatoid arthritis (RA) patients, correlated these with disease activity score (DAS), and examined how they were affected by different therapies, conventional or biological (anti-TNF, anti-CD20 and anti-IL6R or Ig-CTLA4). The percentage of CD4+CD45R0+CD26- cells was greatly reduced in patients (up to 50%) when compared with healthy subjects. Three other subsets of CD4 cells, including a CD26high Th1-associated population, changed variably with therapies. Data from these subsets (frequency and staining density) significantly correlated with DAS28 or DAS28 components but different in each group of patients undergoing the different therapies. Th17 and Th22 subsets were implicated in RA as independent CCR4+ and CCR4- populations each, with distinct CD26 expression, and were targeted with varying efficiency by each therapy. Serum DPP-IV activity rather than sCD26 levels was lower in RA patients compared to healthy donors. DPP-IV and sCD26 serum levels were found related to specific T cell subsets but not to disease activity. We conclude that, according to their CD26 expression, different cell subsets could serve to monitor RA course, and an uncharacterized T helper CD26- subset, not targeted by therapies, should be monitored for early diagnosis.